Acetaldehyde–Ammonia Interaction: A DFT Study of Reaction Mechanism and Product Identification; Journal of Physical Chemistry A; Vol. 121, iss. 16 - Tuguldurova V. P. Vera; Fateev A. V. Aleksandr Vladimirovich; Malkov V. S. Viktor Sergeevich; Poleshchuk O. Kh. Oleg Khemovich; Vodyankina O. V. Olga Vladimirovna (2017, 2017)
Title screen